2007
DOI: 10.1130/g23718a.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and geometry of active detachment faulting beneath the Trans-Atlantic Geotraverse (TAG) hydrothermal field on the Mid-Atlantic Ridge

Abstract: Newly acquired seismic refraction and microearthquake data from the TransAtlantic Geotraverse (TAG) segment of the Mid-Atlantic Ridge at 26°N reveal for the fi rst time the geometry and seismic character of an active oceanic detachment fault. Hypocenters from 19,232 microearthquakes observed during an eight month ocean bottom seismometer deployment form an ~15-km-long, dome-shaped fault surface that penetrates to depths >7 km below the seafl oor on a steeply dipping (~70°) interface. A tomographic model of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
331
4
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 273 publications
(368 citation statements)
references
References 32 publications
31
331
4
2
Order By: Relevance
“…The absence of a crustal melt reservoir and the extension of microearthquake activity (and thus the brittle-plastic rheological transition) to depths greater than 7 km suggest that hydrothermal fluids penetrate much deeper into the lithosphere than previously supposed deMartin et al, 2007).…”
Section: The Role Of the Detachment Faultmentioning
confidence: 83%
See 3 more Smart Citations
“…The absence of a crustal melt reservoir and the extension of microearthquake activity (and thus the brittle-plastic rheological transition) to depths greater than 7 km suggest that hydrothermal fluids penetrate much deeper into the lithosphere than previously supposed deMartin et al, 2007).…”
Section: The Role Of the Detachment Faultmentioning
confidence: 83%
“…Over the last ten years, however, geophysical studies have revealed that the TAG hydrothermal field is located on the hanging wall of an active detachment fault (Tivey et al, 2003;Canales et al, 2007;deMartin et al, 2007). This finding has major implications for our understanding of hydrothermal circulation at slow-spreading mid-ocean ridges.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…An 8-month microseismic experiment at the TAG hydrothermal field (26.1°N) shows deformation along the active detachment fault accommodated by continuous creep associated with steady hydroacoustic event rates (Figure 1d). Microseismicity events at ridge sections with active detachments (TAG 13,15 , 23°N 16 ) are observed down to 7-8 km below seafloor, with the interpreted fault rooting directly below the neovolcanic zone 13 . In contrast, at the centre of symmetrical segments (35°N 17 and Figure 1b, 29°N 18 ) events extend to maximum depths of 5-6 km, 1-3 km shallower than near detachments (see There is a close association of hydrothermal activity and asymmetrical accretion.…”
mentioning
confidence: 99%